The analysis of speech acts patterns in two Egyptian inaugural speeches - Imad Hayif Sameer (Universitas Syiah Kuala, 2017)
The theory of speech acts, which clarifies what people do when they speak, is not about individual words or sentences that form the basic elements of human communication, but rather about particular speech acts that are performed when uttering words. A speech act is the attempt at doing something purely by speaking. Many things can be done by speaking. Speech acts are studied under what is called speech act theory, and belong to the domain of pragmatics. In this paper, two Egyptian inaugural speeches from El-Sadat and El-Sisi, belonging to different periods were analyzed to find out whether there were differences within this genre in the same culture or not. The study showed that there was a very small difference between these two speeches which were analyzed according to Searle’s theory of speech acts. In El Sadat’s speech, commissives came to occupy the first place. Meanwhile, in El–Sisi’s speech, assertives occupied the first place. Within the speeches of one culture, we can find that the differences depended on the circumstances that surrounded the elections of the Presidents at the time. Speech acts were tools they used to convey what they wanted and to obtain support from their audiences.